Spatio-Temporal Biodiversity Data Model Using Object Relational Modeling Approach - Wahid, Mohd. Taib; Mohammed Sharif, Abdur Rashid; Napis, Suhaimi; Ahmad, Noordin (2005)
The complexity of natural history collection information and similar information within the scope of biodiversity informatics poses significant challenges for effective management of plant biodiversity data through database system. Nowadays, many applications need data modeling facilities for the description of complex objects with spatial and/or temporal facilities. Response to such requirements maybe found in Geographic Information Systems (GIS), in some other DBMS, or in other research area. A Geographical Information System (GIS) and its associated data sets are very powerful tools for mapping biodiversity and the intention of this paper is to demonstrate this using three important GIS functions: analysis, data integration, and data visualisation. Some others traditional database systems which are widely used for commercial applications but those models fail to meet biological application (biodiversity data). However, most of existing models cover only partly requirements either spatial or temporal modeling. Beside the commercial applications, there are few models have been designed for biodiversity data management (e.g., OSHADI, BODHI, APASD) but those models are relational model only handle information about biodiversity data does not support analysis, monitoring, manipulation and prediction. Integration between biodiversity data model and GIS data model can make enhancement for the biodiversity data model to make analysis, manipulation. This paper proposes object relational data modeling approach for spatio-temporal biodiversity data model.